2011
DOI: 10.1111/j.2042-3306.2011.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of N‐butylscopolammonium bromide and xylazine in horses

Abstract: SummaryReasons for performing study: N-butylscopolammonium bromide (NBB) and xylazine are commonly used medications for the treatment of spasmodic colic and other forms of abdominal pain in horses. Both NBB and xylazine exert significant effects on the cardiovascular system and other vital systems of horses. Objective: To evaluate the effects of i.v. administration of NBB, xylazine, and the combination of NBB and xylazine on heart rate, other commonly measured physiological parameters, cardiac rhythm and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…; Morton et al. ). In the present study, hyoscine IV increased HR above baseline for 20 minutes, and IM administration increased HR at T15–T30.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Morton et al. ). In the present study, hyoscine IV increased HR above baseline for 20 minutes, and IM administration increased HR at T15–T30.…”
Section: Discussionmentioning
confidence: 99%
“…; Morton et al. ). Hypertension was associated with increased peripheral vascular resistance (Bryant et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, selective M 1 receptor antagonist, telenzepine, was ineffective in improving airway function in human COPD patients (Ukena et al ., ). However, a mixed M 1 /M 3 antagonist might be a promising therapeutic tool in order to achieve good bronchodilation while minimizing side effects due to M 2 activation, like tachycardia (Morton et al ., ). Accordingly, tiotropium, an anticholinergic drug endowed with high M 1 /M 3 kinetic selectivity, resulted more effective than nonselective ipratropium in a clinical trial on human patients with COPD (Lee et al ., ), and revatropate, a selective M 1 /M 3 antagonist, showed excellent bronchodilatant activity and few adverse effects in humans and horses (Lee et al ., ; Morton et al ., ; McGorum et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Lignocaine has been shown to have in vitro effects on jejunal smooth muscle [36], but although it is widely used as an anti-inflammatory agent in equine critical patients, in an experimental model no significant differences were found in inflammatory gene expression in lignocaine-treated and control groups in the black walnut extract model of laminitis, calling into question its use as an anti-inflammatory. Likewise, the ideal analgesic for use in colic patients has yet to be established; both xylazine and N-butylscopolammonium bromide have significant cardiovascular effects, which may, at the very least, influence clinical findings, and their effects should be borne in mind when assessing the colicking horse [37]. Opiates have traditionally been avoided for fear of potential adverse effects on gastrointestinal motility, but a recent study has shown that selective m agonists, without anticholinergic activity, may have less risk than other opiates, but again these studies are based on in vitro work and do not yet translate to clinical practice.…”
Section: Can We Treat Our Colic Cases More Effectively?mentioning
confidence: 99%